Effect of reformation of gas hydrate on the gas phase permeability of montmorillonite. (February 2019) - Li, Yanghui; Wu, Zhaoran; Liu, Weiguo; Luo, Tingting; Song, Yongchen
Abstract: Permeability is one of the key parameters to determine the process of gas hydrate exploitation. The relationship between the gas hydrate reformation and permeability of gas hydrate-bearing sediments is the basic work of marine hydrate reservoir exploration and development. In this paper, the effect of reformation of natural gas hydrate on the gas phase permeability of montmorillonite was investigated. In the experiment, the marine gas hydrate-bearing clayey sediments were simulated by montmorillonite. And series of experiments were performed to investigate the gas phase permeability of montmorillonite with different hydrate saturations after gas hydrate formation and reformation. According to the results, it is found that the gas phase permeability of montmorillonite increased significantly with the reformation of gas hydrate. And after reformation of hydrate, the gas phase permeability of montmorillonite is larger than that of montmorillonite after the initial formation of hydrate. In addition, with the increase of initial hydrate saturation, the increasing ratio of montmorillonite gas phase permeability increases gradually after the reformation of gas hydrate. The results of this research play an important role in the safe and efficient exploitation of marine gas hydrates in the future.